Missional church and local constraints: A Dutch perspective - Rein Brouwer (Verbum et Ecclesia, 2009)
The missional church concept promises to guide local churches in the direction of a new identity and mission. It is a response to a sense of ecclesiological and congregational urgency that is felt all over the world. In Africa, North America and Europe, churches and local faith communities have been challenged by the changes in the religious state of affairs since the 1960s. Whether we still call it secularisation or rephrase it as differentiated transformation, the face of religion is changing globally. In many parts of the world, this raises a feeling of crisis that gives way to the redef nition of the mission and purpose of the church. Missional church, however, is a precarious concept. Nobody disagrees with the intention but can it be more than an inspiring vision? In order to realise this vision, a multi-layered and multi-dimensional analysis of culture is essential. We should move the analysis beyond the philosophical interpretation of relatively abstract and evasive macro-level processes, such as modernity and post-modernity. The future of the missional church depends on a differentiated and empirical, informed perspective on culture. For this purpose, this article proposes the concept of ecology: A system of diverse populations, including populations of congregations and faith communities, that interacts with these populations and with their specific environments. Preparing a missional congregation for the future should be accompanied with a thorough empirical investigation into the ecology of the congregation. We should be thinking intensively about and looking for vital ecologies.